Evaluating the Efficacy of Emotional Intelligence Training versus Gradual Desensitization Methods for individuals with Social Phobia Disorder - Hoseinpur, Nasrin; Dabbaghha, Zahra; Golchin, Mahsa; Amini, Zeinab; Khodadadi, Mitra (Shahroud Journal of Medical Sciences, 2025)
Background and purpose: Social phobia disorder, a pervasive and costly condition, often exhibits a weaker recovery rate compared to other phobia disorders in the absence of effective interventions, leading to a chronic course. This study aimed to compare the effectiveness of emotional intelligence training and gradual desensitization techniques in the treatment of clients with social phobia disorder.